The Architectural Review for the Artist & Craftsman : a Magazine of Architecture and Decoration (ondertitel varieert: A Magazine for the Artist, Archaeologist, Designer and Craftsman)(voortgezet als: Architectural Review (vanaf 1902)) - Hastings, Percy (London : Architectural Press, 1896)
Monthly. Launched in 1896 as The Architectural Review for the Artist and Craftsman by Percy Hastings, owner of the Architectural Press. The Architectural Review is the longest-running and one of the most respected British architectural journals. During the period initially covered by Arts: Search (1896-1910), the focus of the journal was very much on the then prevailing Arts and Crafts style. Contains articles on domestic, commercial, industrial and civic architecture; as well as articles on stained glass; furniture; architectural sculpture; interior decoration, art metalwork; garden design, etc. Architects, designers and craftspeople whose work is discussed and illustrated include C.F.A. Voysey, C.R. Ashbee, M.H. Baillie Scott, and Christopher Whall.(https://www.arthistoryresearch.net/review/the-architectural-review-london.html)
Https://www.architectural-review.com
Engels
Tijdschriften
Keywords: architectuur